Quattro (Carte Romanze, 2020)
Old age concept expressed by Dante in the Commedia and, mostly, the distinction of human life into four ages proposed by the Poet in tratise IV of the Convivio offer the starting point for a series of medical-physiological reflections related to the four elementary qualities and, more extensively, to the hippocratic theory of the four humors, through an exemplification of thirteenth and fourteenth-century texts in vulgar Italian, with fifteenth-century persistence.
Keywords: Dante, Commedia, Convivio, four elementary qualities, theory of the four humors, Hippocrates.